The Effect of Competence and Training on Employee Performance with Work Motivation as a Mediating Variable in Private Manufacturing Companies in Garut Regency - Angga Juanda (SENTRI: Jurnal Riset Ilmiah, 2026)
This study examines the effect of competence and training on employee performance with work motivation as a mediating variable in private manufacturing companies in Garut Regency. Using a quantitative explanatory design, data were collected from 100 permanent employees through structured questionnaires. Structural Equation Modeling based on Partial Least Squares was applied for data analysis. The findings indicate that competence (β = 0.34, p = 0.001) and training (β = 0.28, p = 0.003) significantly affect employee performance. Both competence (β = 0.37, p = 0.000) and training (β = 0.33, p = 0.001) significantly influence work motivation, which in turn significantly affects performance (β = 0.42, p = 0.000). Work motivation partially mediates these relationships. The model demonstrates good fit with SRMR = 0.048 and NFI = 0.93. The study reinforces workplace learning as a practical form of lifelong learning that supports technological adaptation in regional manufacturing industries.